PENGARUH GOOD CORPORATE GOVERNANCE, GREEN ACCOUNTING DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - amelia, Dinda; Anggraini, Anggun; Aditya, Raghil (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
This study aims to examine the influence of good corporate governance, green accounting, and capital structure on firm value. The population in this research consists of non-oil and gas industry companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sampling technique used is purposive sampling, with a total of 36 companies selected as samples. The data employed in this study are secondary data, collected through documentation methods from the official IDX website, www.idx.co.id. . The statistical method applied is panel data regression analysis. The results of the study indicate that good corporate governance and green accounting have a negative effect on firm value. Conversely, capital structure has a positive effect on firm value.